Substantiating the rational parameters and operation modes for the hemp seed centrifugal dehuller - Sheichenko, Viktor; Petrachenko, Dmytro; Koropchenko, Serhii; Rogovskii, Ivan; Gorbenko, Oleksandr; Volianskyi, Mykhailo; Sheichenko, Denys (Eastern-European Journal of Enterprise Technologies, 2024)
The object of research is technological processes, seeds of industrial hemp, and working bodies of the dehuller. A centrifugal-type device for crushing hemp seeds with a closed sector-type working body has been designed. Owing to this, the task related to seed dehulling was solved with a high level of efficiency in separating the seed coat from the kernel. The rational parameters for the dehuller have been substantiated: the diameter of the impeller is 162 mm, the gap between the impeller and the seed repelling panel is 80 mm, the frequency of rotation of the impeller is 2000 min–1. It was established that with the specified parameters and moisture content of the seeds within the limits of conditional (12.0–13.0 %), it is advisable to carry out dehulling process without preliminary separation of the seeds into fractions by width. It was established that an increase in seed size leads to a corresponding increase in the weight share of seed kernels. About 58.2 % of the main mass of seeds is the average fraction with a width of 2.5 to 3.0 mm. It was found that reducing the diameter of the impeller (from 236 mm to 162 mm) at a seed moisture content of 8.8 % improved the efficiency of dehulling. At a rotation frequency of the impeller of 2000 min–1, the highest total number of intact and destroyed kernels (23.23–29.33 %) was achieved for the two studied moistures. With an increase in seed moisture content from 8.8 % to 12.0 %, the number of dehulled kernels in the hempseed cake increased. It was noted that for seeds with a moisture content of 8.8 %, an increase in the gap led to a decrease in the dehulling efficiency for each of the three investigated seed fractions. The total number of dehulled kernels under such conditions decreased by 2.4–6.8 % and amounted to 16.4–26.9 %. For seeds with a moisture content of 12.0 %, an increase in the gap, on the contrary, increased the dehulling efficiency for each of the three investigated seed fractions. The total number of dehulled kernels for seeds of marked moisture increased within the range of 1.4–3.6 % and amounted to 27.4–31.0 %